Business model and business strategy Formulation for ciao - Rendy Irawan, Muhammad; Dung Do, Anh (The Indonesian Journal of Business Administration, 2016)
Abstract - In the recent years many business startups from many industries have emerged, trying to stand out in an already saturated market. Usually, business owners will use the services of designers to help with the choice of room design, lighting and which furniture and appliances to use, in order to make the place as cozy as possible so that people will want to come. This is where other businesses could take advantage of the situation. A variety of businesses could benefit from this opportunity. But then again, that business also has to be unique in order to be able to stand out. Something that would stand out in this area would have to be something that is selling a very unique product; something that business owners could benefit from having instead of using conventional products from other businesses. Selling appliances that not only looks and functions as good as other products, but also incorporates an innovative technology could make more people come to the new store or shop, and help your business to sustain and grow as well. CIAO currently focus on designing 4 products, which are wireless charging-integrated products, smart interactive tables, e-brochures, and a floating table. These products are very one of a kind here and no other company here is known to be making these unique products. CIAO currently is faced with a challenge, which is to educate the customers about the benefits of using unique ways in presenting their product could yield them better results in the long run. Surveys and interviews are used to collect primary data and information about CIAO’s current condition, as well as the current market segment. The results from the survey are then processed through a TOWS matrix to help formulate a strategy based on the strengths, weaknesses, opportunities, and threats. After that, the strategies generated from the TOWS matrix is then used to create a Strategy Diamond and a new business model using a Business Canvas Model. The result of this research shows that CIAO’s current business model does not have the necessary strategy to support its current value proposition. The new strategies formulated in this research suggests CIAO to improve their marketing strategies and focus more on its marketing strategies to establish a distinctive uniqueness among its competitors and in order to sustain as business and continue to grow Keywords:Business Strategy, Business Canvas Model, TOWS Matrix, WirelessCharging, Smart Table